University of Wollongong announced as champions of National Instruments’ autonomous robotic competition - Editors (New Zealand Science Review, 2016)
​ The University of Wollongong (UOW) has won the 2016 National Instruments (NI) Autonomous Robotics Competition. Its Robotics Team beat 25 teams from 19 universities across Australia and New Zealand during the live final at the University of Technology, Sydney, on Monday 26 September. Swinburne University’s team, Swinbots, finished close behind, while the Royal Melbourne Institute of Technology (RMIT) HelpAR team took third place. An award also went to the Western Sydney University (WSU) team, Unlimited Robotics, for having the best-looking robot. ‘We’re incredibly proud of our achievement,’ said UOW’s Shannon Wood. ‘We didn’t expect to win. Instead of prior-itising speed, we focused on a simple and reliable approach that ended up being effective.’ Each year there is a new theme for the competition and, for 2016, the competition’s sixth year, it has been ‘Hospital of the future’. Each autonomous robot navigated a course, completed tasks such as depositing medicine to multiple locations accurately and efficiently, avoiding obstacles, and reaching its final destination with precision. The grand final was opened by a welcome address from Matej Krajnc, Managing Director for National Instruments ANZ/ASEAN, who highlighted the importance of practical experience in science, technology, engineering and mathematics education, and the care and research National Instruments invests in designing materials for students and researchers to use. Special guest Dr Jeannie Falcon, Chief Marketing Engineer for National Instruments, at Austin, Texas, also attended the competition. Guest judges included President of Engineers Australia, Bruce Howards; Uni-versity of Technology Sydney Professor Shoudong Huang, and NI Senior Technical Marketing Engineer, Rejwan Ali. The UOW team were awarded a prize of 2,500, while runners up Swinburne received 1,000 and RMIT took home 500. In addition, WSU received 500 for the best-looking robot. New Zealand entrants from the University of Auckland, Manukau Institute of Technology, Massey University, University of Waikato, and Victoria University of Wellington were unplaced in this year’s competition. In 2013, Victoria University engineering students took out the first prize.